EVALUASI PENATAUSAHAAN BARANG MILIK NEGARA MELALUI PENGGUNAAN APLIKASI SIMAK-BMN PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG MANADO - Karambut, Andrew Malahasa; Morasa, Jenny; Warongan, Jessy D.L (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
This study aims to determine how the Administration of State Property Through the Use of SIMAK-BMN applications at the Office of State Assets and Auction Manado to find out whether the Administration of State Property at the Office of State Assets and Auction Manado is in accordance with the provisions of the applicable regulations in regulating administration BMN. This research is a qualitative descriptive study with the data used in this study are primary data and secondary data. The results of this study indicate that the Office of State Assets and Auction Services in Manado as the Accounting Unit for the Authorization of Goods Users (UAKPB) has carried out the Administration of State Property as well as recording through the use of the SIMAK-BMN application.